Enrichment of Art Subject Content With Research Tasks (Journal of Educational Sciences, 2018)
In the article the system of enriching the content of the subject “Art” is studied through the introductionof research assignments into the structure of each lesson on the basis of one section of the eighthgradeprogram. Scientific and practical novelty lies in the fact that an effective approach to enriching thecontent of education, corresponding to the modern scientific concept of modernization of education, isrevealed on the specific material of the author’s experience, pedagogical conditions for effective enrichmentof the content of the school subject are determined. The practical importance of the work is that theauthor has created a model for enriching the content of the academic subject with a system of researchassignments for students on the lesson, which can be used by teachers of humanitarian disciplines. TheISSN 2520-2634 Journal of Educational Sciences. №1 (54). 2018 95Пaк Е.article discloses the pedagogical conditions for the effective enrichment of the content of the school curriculumwith a system of research assignments.Programming by the teacher of the frequency of different types of research activities in the lessonsoccurs through assignments in which the key guide is the verb that is regulating, that the students exactlyshould do. Now the most frequent research assignments in the practice of conducting lessons in thesubject of “Art” are assignments for the determination:- establish, clarify aspects of the artistic phenomenon, the creative process; – to understand theartistic phenomenon, to solve for themselves a creative issue; – to reveal the essence, the content ofthe work of art, the phenomenon, give a description of art technology, method; – to set the boundariesof actions, assign to a role in the team, micro group; – to place, arrange art works anywhere, a productof visual activity; – to reveal the cause of the appearance of certain phenomena, the conditionality ofartistic effects by technique, material, and instrument of creativity.Key words: the content of school education, the subject “Art”, research tasks, research activities.